Thermal Effect on Void Formation of Waxy Crude Oil Using Electrical Capacitance Tomography (Jurnal Teknologi (Sciences & Engineering), 2013)
Waxy crude oils are commonly found in many parts of the world and represent a huge amount of the global oil reserves. Precipitation of paraffin waxes during various phases creates many problems in the oil industry. Therefore, waxy crude oils create many flow assurance issues essentially linked to them and understanding of the effect of relevant factors and phenomena are of great practical importance. In process industries, the measurement of void fraction is considerably important for sustainable operations and the erroneous calculation could be the cause of many industrial accidents. The customary approach separates the two-phases first and then measures the mixture as individual components. These methods are not favorable as they may result in the disruption of incessant industrial processes. Due to these limitations, this study is aimed to analyze the gel formation behavior of a waxy crude oil under static and dynamic cooling using non-invasive/non-intrusive experimental technique; i.e. Electrical Capacitance Tomography (ECT). This paper describes a fabrication of dual-plane ECT sensor for testing of waxy crude oil at different temperature conditions. ECT images and raw data measurements have been obtained from the two planes are then normalised and then used for image reconstruction. The findings reported in this paper represent part of an ongoing investigation that may lead to develop a cross-correlation between the two planes. The outcome of the study could be used to fully understand the phenomenon of void fraction in waxy crude based on varying the temperature and also based on the design of ECT sensor.